Effect of Obesity and Other Risk Factors on Hypertension among Women of Reproductive Age in Ghana: An Instrumental Variable Probit Model - Oyekale, Abayomi Samuel (Int J Environ Res Public Health, 2019)
Background: The growing incidence of mortality as a result cardiovascular diseases (CVDs) is a major public health concern in several developing countries. In Ghana, unhealthy food consumption pattern and sedentary lifestyle are promoting overweight and obesity, with significant consequences on the incidence of CVDs. Specifically, hypertension morbidity is now a public health concern among Ghanaian health policy makers. This paper analysed the effect of body mass index (BMI)/arm circumference and other associated factors on hypertension risk among women of reproductive ages in Ghana. Methods: The data were collected as Demographic and Health Survey (DHS) in 2014. This paper analysed the subset of the data that were collected from eligible women 15–49 years of age. The total sample was 9396, while 9367 gave consents to have their blood pressure measured. Data were analysed with instrumental probit regression model with consideration of potential endogeneity of BMI and arm circumference. Results: The results showed that 25% of the women were either overweight or obese, while 13.28% were hypertensive. Women from the Greater Accra (18.15%), Ashanti (15.53%) and Volta (15.02%) regions had the highest incidences of hypertension. BMI and arm circumferences were truly endogenous and positively associated with the probability of being hypertensive. Other factors that influenced hypertension were age of women, region of residence, urban/rural residence, being pregnant, access to medical insurance, currently working, consumption of broth cubes, processed can meats, salted meat and fruits. Conclusion: It was concluded that hypertension risk was positively associated with being overweight, obesity, age and consumption of salted meat.It was inter aliaemphasized that engagement in healthy eating with less consumption of salted meats, and more consumption of fruits would assist in controlling hypertension among Ghanaian women.